Dehydrin AmDH1 improves drought tolerance in transgenic maize plants - Thi Thu Hue, Huynh; Quynh Lien, Le; Chi Mai, Nguyen; My Linh, Tran; Manh Minh, Bui (Vietnam Journal of Biotechnology, 2023)
Dehydrin is a large protein group to have protective functions to plant cells under osmotic stress. Overexpression of dehydrin encoded genes isolated from mangrove plants had improved drought tolerance of transgenic plants. Therefore, in this research, a coding sequence with the length of 573bp that encodes Dehydrin1 (DH1) protein was isolated from a mangrove plant namely Mam bien (Avicennia marina) which naturally grows in Xuan Thuy national park, Vietnam. The coding sequence was denoted as AmDH1 and cloned into the plant transformation vector pCAM 35S-AmDH1. The transgenic vector was transformed into A. tumefiaciens cells and the vector was transferred into the K7 maize line to generate transgenic maize seedlings. The AmDH1 transgenic maize T2 seedlings have shown an improved drought tolerance than the original K7 maize line.